2013
DOI: 10.1111/inm.12030
|View full text |Cite
|
Sign up to set email alerts
|

Staff representations and tobacco‐related practices in a psychiatric hospital with an indoor smoking ban

Abstract: The present study describes representations about smoking and practices related to patient smoking among staff of a large public psychiatric hospital. A survey was performed using a specially designed questionnaire. The return rate was 72.4% (n = 155). A large proportion of staff recognized the importance of both smoking status and mental health for patient's well-being (46.9%), and believed that smoking cessation was possible for psychiatric patients (58.6%). However, the role of the psychiatric hospital was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…The majority of the 38 studies were conducted in either Australia (14)(Stanley and Laugharne, 2013; Bartlem et al, 2015; Bartlem et al, 2014a; Happell et al, 2013a; Anderson et al, 2013; Ashton et al, 2010; Siru et al, 2010; Stanton et al, 2015; Stockings et al, 2015; Stockings et al, 2014; Tso et al, 2017; Wye et al, 2010; Wye et al, 2009; Wye et al, 2017) or the USA (11) (Price et al, 2007; Schacht et al, 2012; Chwastiak et al, 2013; Williams et al, 2015; Bolton et al, 2016; Himelhoch et al, 2014; Kilbourne et al, 2011; Leyro et al, 2013; Maki and Bjorklund, 2013; Prochaska et al, 2006; Sarna et al, 2009). Eight described client reported receipt of preventive care, (Bartlem et al, 2015; Etter et al, 2008; Siru et al, 2010; Stockings et al, 2015; Stockings et al, 2014; Leyro et al, 2013; Prochaska et al, 2006; Etter and Etter, 2007) 21 described clinician reported provision of care, (Bartlem et al, 2014a; Happell et al, 2013a; Price et al, 2007; Etter et al, 2008; Schacht et al, 2012; Zabeen et al, 2015; Anderson et al, 2013; Chwastiak et al, 2013; Williams et al, 2015; Ashton et al, 2010; Stanton et al, 2015; Wye et al, 2009; Bolton et al, 2016; Himelhoch et al, 2014; Sarna et al, 2009; Johnson et al, 2009; Haddad et al, 2016; Keizer et al, 2014; Ballbe et al, 2012; Guo et al, 2015; Robson et al, 2013a) and 12 described medical record audit data; (Stanley and Laugharne, 2013; Howard and Gamble, 2011; Williams et al, 2015; Tso et al, 2017; Wye et al, 2010; Wye et al, 2017; Kilbourne et al, 2011; Maki and Bjorklund, 2013; Prochaska et al, 2006; <...>…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the 38 studies were conducted in either Australia (14)(Stanley and Laugharne, 2013; Bartlem et al, 2015; Bartlem et al, 2014a; Happell et al, 2013a; Anderson et al, 2013; Ashton et al, 2010; Siru et al, 2010; Stanton et al, 2015; Stockings et al, 2015; Stockings et al, 2014; Tso et al, 2017; Wye et al, 2010; Wye et al, 2009; Wye et al, 2017) or the USA (11) (Price et al, 2007; Schacht et al, 2012; Chwastiak et al, 2013; Williams et al, 2015; Bolton et al, 2016; Himelhoch et al, 2014; Kilbourne et al, 2011; Leyro et al, 2013; Maki and Bjorklund, 2013; Prochaska et al, 2006; Sarna et al, 2009). Eight described client reported receipt of preventive care, (Bartlem et al, 2015; Etter et al, 2008; Siru et al, 2010; Stockings et al, 2015; Stockings et al, 2014; Leyro et al, 2013; Prochaska et al, 2006; Etter and Etter, 2007) 21 described clinician reported provision of care, (Bartlem et al, 2014a; Happell et al, 2013a; Price et al, 2007; Etter et al, 2008; Schacht et al, 2012; Zabeen et al, 2015; Anderson et al, 2013; Chwastiak et al, 2013; Williams et al, 2015; Ashton et al, 2010; Stanton et al, 2015; Wye et al, 2009; Bolton et al, 2016; Himelhoch et al, 2014; Sarna et al, 2009; Johnson et al, 2009; Haddad et al, 2016; Keizer et al, 2014; Ballbe et al, 2012; Guo et al, 2015; Robson et al, 2013a) and 12 described medical record audit data; (Stanley and Laugharne, 2013; Howard and Gamble, 2011; Williams et al, 2015; Tso et al, 2017; Wye et al, 2010; Wye et al, 2017; Kilbourne et al, 2011; Maki and Bjorklund, 2013; Prochaska et al, 2006; <...>…”
Section: Resultsmentioning
confidence: 99%
“…Rates of 36.1% 13 , 53% 14 or 67% 15 are described in patients with schizophrenia or non-affective psychosis. Although this population accounts for a growing proportion of all smokers 13,16 , barriers prevent optimal interventions 17,18 . The assumption that smoking cessation may be a risk factor for increased psychopathology in psychiatric patients is widespread 19,20 , although most recent studies emphasize the benefits of cessation 21 and the selfmedication hypothesis of smoking is questioned 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Son varias las barreras que interfieren en estas intervenciones; la primera se encuentra en los mismos profesionales al tener presente una idea generalizada de que estos individuos tienen más dificultades para conseguir la abstinencia al tabaco, por lo que no se le aconseja o recomienda dejar de fumar (7) . Otra barrera encontrada es la creencia de que la intervención podría interferir en la abstinencia de otras sustancias (8) a pesar, de que en la literatura se ha descrito que presentan una buena evolución en el pronóstico del tratamiento (9,10) . Una idea muy extendida es que los individuos que abusan de otras sustancias no muestran interés en un tratamiento de desintoxicación del tabaco.…”
Section: Introductionunclassified